Rigid polyamine composite nanofiltration membrane and preparation method thereof

Through the reaction of thionyl chloride and rigid polyamine on the base membrane and competitive functional molecular pretreatment, the problems of high preparation cost and low flux of polyamide composite nanofiltration membrane in the prior art are solved, and low cost and high A composite nanofiltration membrane with flux and double charge characteristics can effectively intercept a variety of charged substances.

CN119186264APending Publication Date: 2024-12-27TIANJIN MOTIMO MEMBRANE TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411242890.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing polyamide composite nanofiltration membrane is expensive to prepare, has a low flux, a narrow range of application, and cannot effectively intercept a variety of charged substances.

Method used

Thionyl chloride is used to react with polyamines with rigid structure on the base membrane, form a composite nanofiltration membrane through volatilization and diffusion, and pretreatment is used to optimize membrane performance.

Benefits of technology

The preparation cost of composite nanofiltration membrane is reduced, the flux and double-charge characteristics of the membrane are improved, and a variety of charged substances can be effectively intercepted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the field of separation, and particularly relates to a rigid polyamine composite nanofiltration membrane and a preparation method thereof. The preparation method comprises the following steps: coating one side of a base membrane with polyamine with a rigid structure, contacting thionyl chloride with the other side of the base membrane, diffusing thionyl chloride to pass through membrane pore channels of the base membrane in a volatilization manner, and contacting with melamine for reaction to prepare the composite nanofiltration membrane. According to the technical scheme, firstly, based on the low price of thionyl chloride, the cost of preparing the composite nanofiltration membrane is low; secondly, by means of the steam reverse mass transfer reaction, the prepared composite nanofiltration membrane has the double-charge characteristic, and most substances with the charge characteristic can be intercepted. In addition, due to the fact that the molecular chain of thionyl chloride is short, the reaction activity with polyamine is weak, the overall aperture of the prepared polyamide composite nanofiltration membrane is larger, and the flux of the prepared nanofiltration membrane is higher.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of separation, and in particular relates to a rigid polyamine composite nanofiltration membrane and a preparation method thereof. Background Art

[0002] Polyamide composite nanofiltration membranes have been widely used in reverse osmosis, nanofiltration, gas separation and other fields, and are usually prepared by reacting polyamines with trimesoyl chloride. However, trimesoyl chloride is expensive, with 500g of trimesoyl chloride costing as high as 1,634 yuan, which greatly increases the preparation cost of composite nanofiltration membranes.

[0003] Therefore, it is necessary to find new low-cost polyacid chlorides to replace them. Thionyl chloride, as a diacid chloride, costs only 76 yuan for 500 ml. At the same time, it is a volatile liquid and can be combined with steam reverse mass transfer reaction to prepare polyamide composite nanofiltration membranes with excellent performance.

[0004] Conventional interfacial polymerization method for preparing hollow fiber composite nanofiltration membranes: first, a polyamine aqueous solution is circulated through the hollow fiber membrane module tube, and the residual water droplets inside the membrane are purged after coating; then, a n-hexane solution of trimesoyl chloride is unidirectionally passed through the hollow fiber membrane module tube, and reacted at room temperature for a certain period of time to prepare a hollow fiber composite nanofiltration membrane. However, this method has a narrow scope of application for preparing hollow fiber composite nanofiltration membranes and is only suitable for the retention of single-charge substances. In addition, the oil phase monomer trimesoyl chloride is expensive, and the amount of n-hexane used is large, resulting in a high cost for preparing nanofiltration membranes. At the same time, since trimesoyl chloride has many reaction sites and high reaction activity, the overall pore size of the prepared hollow fiber composite nanofiltration membrane is small, and the corresponding prepared composite nanofiltration membrane flux is low. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a rigid polyamine composite nanofiltration membrane and a preparation method thereof.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing a rigid polyamine composite nanofiltration membrane comprises the following steps: coating a polyamine having a rigid structure on one side of a base membrane, contacting thionyl chloride with the other side of the base membrane, diffusing thionyl chloride through the membrane pore channel of the base membrane by volatilization, and reacting with the polyamine having a rigid structure to obtain a composite nanofiltration membrane

[0008] The polyamine with a rigid structure is one of melamine, 9,9-bis(4-aminophenyl)fluorene, tetrakis(4-aminophenyl)methane and 2,2'-benzidine disulfonic acid.

[0009] The base film is pretreated before being coated with a polyamine having a rigid structure; the pretreatment method is to use competitive functional molecules for coating; the competitive functional molecules are polyvinyl alcohol, hydroxyethyl cellulose, or dopamine.

[0010] The method for preparing a rigid polyamine composite nanofiltration membrane comprises the following steps: 1) introducing an aqueous solution of a polyamine containing a rigid structure into the tube side of a membrane component; 2) introducing thionyl chloride into and filling the shell side of the membrane component, and letting it stand for a certain period of time to obtain the desired composite nanofiltration membrane.

[0011] The mass concentration of the aqueous solution of the polyamine containing a rigid structure in step 1) is 0.1-0.3%.

[0012] The standing time of step 2) is 1-10 min.

[0013] The specific method of using competitive functional molecules for coating is: circulating the competitive functional molecule aqueous solution into the membrane component, and after circulating for a period of time, cleaning the membrane component and drying it.

[0014] The mass concentration of the competitive functional molecule aqueous solution is 0.1-0.5%, preferably 0.3%.

[0015] The cycle time is 20-60 min, preferably 30 min.

[0016] The base membrane of the membrane assembly is a hydrophobic base membrane; preferably, the material of the base membrane of the membrane assembly is one of PVC, PVDF, PTFE, PVDF-CTFE, CTFE or a mixture thereof.

[0017] The present invention also includes a rigid polyamine composite nanofiltration membrane obtained by the preparation method.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The technical solution of the present application is based on the price of thionyl chloride, and the cost of the prepared composite nanofiltration membrane is low. Secondly, by utilizing its steam reverse mass transfer reaction, the obtained composite nanofiltration membrane has a dual-charge characteristic, which can intercept most of the substances with charge characteristics. Furthermore, since the thionyl chloride molecular chain is short and the reaction activity with polyamine is weak, the overall pore size of the prepared polyamide composite nanofiltration membrane is larger, and the flux of the prepared nanofiltration membrane is higher. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the best embodiment.

[0021] A method for preparing a rigid polyamine composite nanofiltration membrane comprises the following steps: coating a polyamine having a rigid structure on one side of a base membrane, contacting thionyl chloride with the other side of the base membrane, and diffusing thionyl chloride through the membrane pores of the base membrane by volatilization to react with the polyamine having a rigid structure to obtain a composite nanofiltration membrane.

[0022] The rigid structure polyamine is one of melamine, 9,9-bis(4-aminophenyl)fluorene, tetrakis(4-aminophenyl)methane, and 2,2'-benzidine disulfonic acid. In this application, melamine is used as an example.

[0023] The base film is pretreated before coating with a polyamine having a rigid structure; the pretreatment method is to coat with a competitive functional molecule; the competitive functional molecule is polyvinyl alcohol, hydroxyethyl cellulose, or dopamine. In this application, polyvinyl alcohol (molecular weight of 10000Da) is used as an example.

[0024] The preparation method of a rigid polyamine composite nanofiltration membrane comprises the following steps: 1) introducing an aqueous solution containing a polyamine with a rigid structure into the tube side of the membrane assembly; 2) introducing thionyl chloride into the shell side of the membrane assembly and filling it, and letting it stand for a certain time to obtain the desired composite nanofiltration membrane. The mass concentration of the aqueous solution containing a polyamine with a rigid structure in step 1) is 0.1-0.3%. The standing time in step 2) is 1-10 minutes.

[0025] The specific method of using competitive functional molecules for coating is: circulating the competitive functional molecule aqueous solution into the membrane assembly, and after circulating for a period of time, cleaning the membrane assembly and drying. The mass concentration of the competitive functional molecule aqueous solution is 0.1-0.5%, preferably 0.3%. The circulation time is 20-60 minutes, preferably 30 minutes.

[0026] The base membrane of the membrane assembly is a hydrophobic base membrane; preferably, the material of the base membrane of the membrane assembly is one of PVC, PVDF, PTFE, PVDF-CTFE, CTFE or a mixture thereof.

[0027] The present invention also includes a rigid polyamine composite nanofiltration membrane obtained by the preparation method.

[0028] The following is an explanation with reference to specific embodiments.

[0029] Example 1

[0030] The preparation method of melamine composite nanofiltration membrane comprises the following steps: introducing a 0.2wt% melamine aqueous solution into the tube side of a dry hydrophobic PVDF hollow fiber membrane module; then introducing and filling thionyl chloride into the shell side of the membrane module, and standing at room temperature for 2 minutes to react; finally, obtaining a cross-linked melamine composite nanofiltration membrane. Before the membrane performance test, the membrane is first wetted and cleaned with ethanol, and then the ethanol in the membrane pores is replaced with deionized water.

[0031] Example 2

[0032] The preparation method of melamine composite nanofiltration membrane comprises the following steps: introducing a 0.1wt% melamine aqueous solution into the tube side of a dry hydrophobic PVDF hollow fiber membrane module; then introducing and filling thionyl chloride into the shell side of the membrane module, and standing at room temperature for 2 minutes to react; finally, obtaining a cross-linked melamine composite nanofiltration membrane. Before the membrane performance test, the membrane is first wetted and cleaned with ethanol, and then the ethanol in the membrane pores is replaced with deionized water.

[0033] Example 3

[0034] The preparation method of the melamine composite nanofiltration membrane comprises the following steps: introducing a 0.25 wt% melamine aqueous solution into the tube side of a dry hydrophobic PVDF hollow fiber membrane module; then introducing and filling thionyl chloride into the shell side of the membrane module, and standing at room temperature for 2 minutes to react; finally, obtaining a cross-linked melamine composite nanofiltration membrane. Before the membrane performance test, the membrane is first wetted and cleaned with ethanol, and then the ethanol in the membrane pores is replaced with deionized water.

[0035] Example 4

[0036] The preparation method of melamine composite nanofiltration membrane comprises the following steps: introducing a 0.3wt% melamine aqueous solution into the tube side of a dry hydrophobic PVDF hollow fiber membrane module; then introducing and filling thionyl chloride into the shell side of the membrane module, and standing at room temperature for 2 minutes to react; finally, obtaining a cross-linked melamine composite nanofiltration membrane. Before the membrane performance test, the membrane is first wetted and cleaned with ethanol, and then the ethanol in the membrane pores is replaced with deionized water.

[0037] Example 5

[0038] The preparation method of melamine composite nanofiltration membrane includes the following steps: first, modifying the inner surface of PVDF membrane, that is, circulating 0.3wt% polyvinyl alcohol solution into the tube side of PVDF hollow fiber membrane module at room temperature, and after circulating for 30 minutes, cleaning the membrane module and drying it. Then, passing 0.2wt% melamine aqueous solution into the tube side of the dry composite hydrophobic PVDF hollow fiber membrane module; then, passing and filling thionyl chloride into the shell side of the membrane module, and standing at room temperature for 10 minutes; finally, obtaining a cross-linked melamine-polyvinyl alcohol composite nanofiltration membrane. Before the membrane performance test, the membrane is first wetted and cleaned with ethanol, and then the ethanol in the membrane pores is replaced with deionized water.

[0039] Example 6

[0040] The preparation method of melamine composite nanofiltration membrane includes the following steps: first, modifying the inner surface of the PVDF membrane, that is, circulating a 0.2wt% polyvinyl alcohol solution into the tube side of the PVDF hollow fiber membrane module at room temperature, and after circulating for 30 minutes, cleaning the membrane module and drying it. Then, passing a 0.2wt% melamine aqueous solution into the tube side of the dry composite hydrophobic PVDF hollow fiber membrane module; then, passing and filling thionyl chloride into the shell side of the membrane module, and standing at room temperature for 10 minutes to react; finally, obtaining a cross-linked melamine-polyvinyl alcohol composite nanofiltration membrane. Before the membrane performance test, the membrane is first wetted and cleaned with ethanol, and then the ethanol in the membrane pores is replaced with deionized water.

[0041] Example 7

[0042] The preparation method of melamine composite nanofiltration membrane includes the following steps: first, modifying the inner surface of the PVDF membrane, that is, circulating a 0.4wt% polyvinyl alcohol solution into the tube side of the PVDF hollow fiber membrane module at room temperature, and after circulating for 30 minutes, cleaning the membrane module and drying it. Then, passing a 0.2wt% melamine aqueous solution into the tube side of the dry composite hydrophobic PVDF hollow fiber membrane module; then, passing and filling thionyl chloride into the shell side of the membrane module, and standing at room temperature for 10 minutes to react; finally, obtaining a cross-linked melamine-polyvinyl alcohol composite nanofiltration membrane. Before the membrane performance test, the membrane is first wetted and cleaned with ethanol, and then the ethanol in the membrane pores is replaced with deionized water.

[0043] Comparative Example 1

[0044] Preparation of conventional polyamide nanofiltration membrane: First, a 0.2wt% melamine aqueous solution was passed from bottom to top through the tube of the PVC hollow fiber membrane module using a peristaltic pump. After soaking for 5 minutes, an air compressor was used to purge the membrane module tube from top to bottom at a linear speed of 13.0m / s to remove excess aqueous solution. The purge time was 5 minutes. Then, a 0.15wt% trimesoyl chloride n-hexane solution was passed from bottom to top using a peristaltic pump and reacted for 1 minute to prepare a hollow fiber polyamide nanofiltration membrane. After the experiment, the prepared nanofiltration membrane was stored in deionized water for testing.

[0045] Table 1 Performance test results of melamine-thionyl chloride composite nanofiltration membrane prepared by the present invention

[0046]

[0047] Result analysis:

[0048] The nanofiltration membrane assembly prepared in the embodiment and the comparative example was fixed on a cross-flow filtration test device. Pure water passed through the membrane assembly under the internal pressure mode. The pressure of the cross-flow filtration test device was set at 0.40 MPa for pre-compression for 1 h. After the membrane was completely compacted, the test was performed at 0.30 MPa. The water obtained within 10 min was collected and the pure water flux was tested by weighing method. Then the pure water was replaced with 1.0 g / L MgCl 2 Or Na 2 SO 4 The solution was used as the feed solution for further testing. The salt solution passed through the membrane assembly under internal pressure mode. The operating pressure of the cross-flow filtration test device was 0.30 MPa. The salt concentration in the produced water was tested using a conductivity meter every 10 minutes until the conductivity of the produced water remained stable. The salt retention rate of the nanofiltration membrane was calculated.

[0049] Analysis of the results of Examples 1-4: As the concentration of melamine in the aqueous phase increases, more melamine molecules react with the volatilized thionyl chloride molecules during the steam reverse mass transfer reaction, making the cross-linked melamine composite nanofiltration membrane more effective for MgCl 2 The interception rate showed a trend of gradual increase, while Na 2 SO 4 The retention rate gradually decreases due to the increase in the amount of positive charge on the membrane surface. Based on the reverse mass transfer mechanism and the above salt retention test results, it can be determined that the top of the separation layer has a strong positive charge characteristic, while the bottom of the separation layer has a strong negative charge characteristic, that is, the present invention successfully prepares a separation layer with dual charge characteristics.

[0050] Analysis of the results of Example 5 and Example 1: After the polyvinyl alcohol coating treatment on the base membrane, the flux of the composite nanofiltration membrane was further improved. This is because polyvinyl alcohol also reacts with thionyl chloride, destroying the regular pore structure formed by the reaction between melamine and thionyl chloride, making the pore size of the composite nanofiltration membrane larger. In addition, after the polyvinyl alcohol coating treatment on the base membrane, the MgCl 2 The retention rate also increased. This was due to the competitive reaction between polyvinyl alcohol and melamine, which resulted in a decrease in the amount of reaction between the amine groups of melamine and the acyl chloride groups, leaving more positively charged amine groups remaining on the membrane surface.

[0051] Comparative analysis of Example 1 and Comparative Example 1: Compared with the polyamide composite nanofiltration membrane prepared by the conventional interfacial polymerization process of Comparative Example 1, the composite nanofiltration membrane prepared by Example 1 has a higher flux result. This is because the reaction activity of thionyl chloride is low, and accordingly, the pore size of the prepared polyamide composite nanofiltration membrane is larger. At the same time, there is a self-inhibition effect in the reverse mass transfer reaction, resulting in a thinner thickness of the prepared separation layer. As a result, the flux of the composite nanofiltration membrane prepared in Example 1 is as high as 24.5 L·m -2 ·h -1 bar -1 In addition, Comparative Example 1 is a polyamide nanofiltration membrane prepared by conventional interfacial polymerization. During the aqueous coating process, the amount of amine groups stored on the surface of the base membrane is limited, which makes it difficult to form a dual-charge separation layer. Therefore, the composite nanofiltration membrane prepared by conventional interfacial polymerization is not suitable for MgCl 2 The interception rate is only 83.2%, which is much lower than that of the composite nanofiltration membrane prepared by the present invention.

[0052] The results of Example 5, Example 6 and Example 7 are analyzed as follows: As the concentration of polyvinyl alcohol increases, the amount of polyvinyl alcohol involved in the reaction gradually increases, and the membrane pore size gradually increases, so that the flux of the prepared nanofiltration membrane gradually increases. Among them, when the concentration of polyvinyl alcohol increases to 0.4wt%, the overall pore size of the prepared nanofiltration membrane increases significantly, resulting in a significant decrease in the salt rejection rate of the nanofiltration membrane. When the concentration of polyvinyl alcohol is 0.3wt%, the performance of the prepared nanofiltration membrane is optimal.

[0053] The technical solution of the present application is based on the low price of thionyl chloride, and the cost of the prepared composite nanofiltration membrane is low. Secondly, by utilizing its steam reverse mass transfer reaction, the prepared composite nanofiltration membrane has a dual-charge characteristic, which can intercept most of the substances with charge characteristics. Furthermore, since the thionyl chloride molecular chain is short and the reaction activity with polyamine is weak, the overall pore size of the prepared polyamide composite nanofiltration membrane is larger, and the flux of the prepared nanofiltration membrane is higher.

[0054] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a rigid polyamine composite nanofiltration membrane, characterized in that: The method comprises the following steps: coating a polyamine with a rigid structure on one side of a base membrane, and then bringing thionyl chloride into contact with the other side of the base membrane, wherein the thionyl chloride diffuses through the membrane pore channel of the base membrane in a volatilization manner, and contacts and reacts with the polyamine with the rigid structure to obtain a composite nanofiltration membrane.

2. The method for preparing a rigid polyamine composite nanofiltration membrane according to claim 1, characterized in that: The polyamine with a rigid structure is one of melamine, 9,9-bis(4-aminophenyl)fluorene, tetrakis(4-aminophenyl)methane and 2,2'-benzidine disulfonic acid.

3. The method for preparing a rigid polyamine composite nanofiltration membrane according to claim 1, characterized in that: The base film is pretreated before being coated with a polyamine having a rigid structure; the pretreatment method is to use competitive functional molecules for coating; the competitive functional molecules are polyvinyl alcohol, hydroxyethyl cellulose, or dopamine.

4. The method for preparing the rigid polyamine composite nanofiltration membrane according to claim 1, characterized in that: The method comprises the following steps: 1) introducing an aqueous solution containing a polyamine with a rigid structure into the tube side of the membrane component; 2) introducing thionyl chloride into the shell side of the membrane component and filling the shell side with thionyl chloride, and standing the shell side for a certain period of time to react, thereby obtaining a desired composite nanofiltration membrane.

5. The method for preparing a rigid polyamine composite nanofiltration membrane according to claim 4, characterized in that: The mass concentration of the aqueous solution of the polyamine containing a rigid structure in step 1) is 0.1-0.3%; preferably, the static reaction time in step 2) is 1-10 minutes.

6. The method for preparing a rigid polyamine composite nanofiltration membrane according to claim 3, characterized in that: The specific method of using polyvinyl alcohol for coating is: circulating the competitive functional molecule aqueous solution into the membrane component, and after circulating for a period of time, cleaning the membrane component and drying it.

7. The method for preparing a rigid polyamine composite nanofiltration membrane according to claim 6, characterized in that: The mass concentration of the competitive functional molecule aqueous solution is 0.1-0.5%, preferably 0.3%.

8. The method for preparing a rigid polyamine composite nanofiltration membrane according to claim 6, characterized in that: The cycle time is 20-60 min, preferably 30 min.

9. The method for preparing a rigid polyamine composite nanofiltration membrane according to claim 1, characterized in that: The base membrane of the membrane assembly is a hydrophobic base membrane; preferably, the material of the base membrane of the membrane assembly is one of PVC, PVDF, PTFE, PVDF-CTFE, CTFE or a mixture thereof.

10. A rigid polyamine composite nanofiltration membrane obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Preparation method of polyamide nanofiltration membrane capable of avoiding acyl chloride hydrolysis influence

    CN120079253A